SOUTH AFRICAN ARMY RANKS AND INSIGNIA - Radburn, Athur (Scientia Militaria - South African Journal of Military Studies, 2012)
Like many other aspects of South Africa's military tradition, our rank system is derived from that of the British Army. It has, however, been modified and developed over the years to suit our own particular requirements, and has become a distinctive system in its own right. This article is a brief survey of developments since the army was organised in 1912.